2016
DOI: 10.1002/chin.201612180
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Oxidative Cross‐Coupling of sp3‐ and sp2‐Hybridized C—H Bonds: Vanadium‐Catalyzed Aminomethylation of Imidazo[1,2‐a]pyridines.

Abstract: Oxidative Cross-Coupling of sp 3 -and sp 2 -Hybridized C-H Bonds: Vanadium-Catalyzed Aminomethylation of Imidazo[1,2-a]pyridines. -In addition to the coupling of substituted imidazo[1,2-a]pyridines with N-methylmorpholine oxide, the corresponding coupling of indoles is successfully performed. -(KASWAN, P.; PORTER, A.; PERICHERLA, K.; SIMONE, M.; PETERS, S.; KUMAR*, A.; DEBOEF, B.; Org. Lett. 17 (2015) 21, 5208-5211, http://dx.doi.org/10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Very recently, Kumar, DeBoef, and co-workers have also reported on a protocol for the oxidative coupling of C(sp 2 )−H and C(sp 3 )−H using VO(acac) 2 as the catalyst. 358 For The direct functionalization of saturated hydrocarbons to valuable products, such as alcohols, ketones, and carboxylic acids, is among the most attractive and challenging task in academic and industrial research. 361 In this context, vanadium complexes are well known to oxidize hydrocarbons in the presence of oxygen and/or peroxides.…”
Section: Oxidative Coupling Of Phenols and Relatedmentioning
confidence: 99%
“…Very recently, Kumar, DeBoef, and co-workers have also reported on a protocol for the oxidative coupling of C(sp 2 )−H and C(sp 3 )−H using VO(acac) 2 as the catalyst. 358 For The direct functionalization of saturated hydrocarbons to valuable products, such as alcohols, ketones, and carboxylic acids, is among the most attractive and challenging task in academic and industrial research. 361 In this context, vanadium complexes are well known to oxidize hydrocarbons in the presence of oxygen and/or peroxides.…”
Section: Oxidative Coupling Of Phenols and Relatedmentioning
confidence: 99%
“…This aminomethylation process was extended to heterocycles such as imidazo[1,2-a]pyridines and indole by DeBoef and coworkers in 2015 (Scheme 54). 316 The authors reported that the same regiochemical outcome is obtained in a conventional Mannich alkylation with morpholine and paraformaldehyde. Additionally, the reaction is unperturbed by the addition of TEMPO as a radical inhibitor.…”
Section: Carbon−carbon Bond Formationmentioning
confidence: 99%